Upgrading the Employment Scene in Chicago - Gerald D. Bailey; LaVisa Wilson (Educational Considerations, 1973)
Appalled at the degree to which employment interviews at the annual AACTE convention too often seem cold, aloof, and negative, educators Bailey and Wilson offer suggestions to help rehumanize the process.